PENINGKATAN KETERAMPILAN MENYIMAK MENGGUNAKAN MEDIA AUDIO DI SEKOLAH DASAR - Wulandary, Yuliana; Halidjah, Siti; Margiyati, K.Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractListening skill is a series of activities that students do to understand the set of ideas contained through teacher guidance. The general problem, whether the use of audio media can improve the skills of listening to children's fiction stories on students of grade V SDN 33 South Pontianak. Aims to improve the skills of children's fictional stories by using audio media in grade V students.This research uses descriptive method, form of action research class (PTK) and is collaborative. Subjects in this study were researchers as teachers and students of VA class which amounted to 32 students. The study was conducted in the odd semester. The procedures used are planning, implementation, observation and reflection. Techniques used are observation and scrutiny of documents, data collection tool is an observation sheet and document scrutiny sheet. Data analysis was conducted between researcher and observer collaboration. The result of skill study of children's fiction story using audio media in cycle I got the average score of 73.75. In cycle II the average score 84.84. In cycle III get an average value of 86.87. In the IV cycle obtained an average value of 90.15. And has reached the success indicator with the value of the provision 80.It can be concluded that using audio media can improve the skill of listening to children's fiction story on VA grade students of State Elementary School 33 South Pontianak.Â Keywords: Listening Skills, Audio Media